School Management and Technical Support to Teachers and Students in the Integration of ICT in Teaching/Learning English Language - Atyang, Florence; Gathumbi, Agnes; Babusa, Hamisi (Advances in Social Sciences Research Journal, 2018)
Information Communication and Technology (ICT) has been used in almost all fields of life. In Kenya, ICT has become so essential that the Kenya government has invested substantially in providing the requisite resources in schools. The utilization of ICT in education has recently started to appeal to the potential and significant progress in education. The process of integrating ICT into teaching and learning is an intricate process and its success or failure depends on a number of factors. These could mainly be teacher and institutional related. This study sought to investigate the use of ICT in the teaching of English language in Bungoma secondary schools in Kenya. The study adopted a descriptive survey design. The target population comprised 51 secondary schools, out of which 11 that have had computers for some time were selected. Combinations of stratified, random and purposive sampling procedures were used. The samples comprised 11 secondary school principals, 48 teachers of English, and 385 form three students: 190 girls and 195 boys. Data were collected using questionnaires, a lesson observation schedule and an interview schedule. A pilot study was carried out to determine the reliability and validity of the research instruments as well as the feasibility of the study. Data collected in the main study were analysed using the Statistical Package for Social Sciences (SPSS) version 21.0. Descriptive statistics comprising frequency counts, means and percentages were utilised in the analysis of the gathered data. The main findings of the study indicated: management and technical support were moderate, mainly in the provision of some ICT facilities and employment of computer teachers. The use of ICT in lesson delivery was low due to a number of factors: inadequate facilities and time to access computers, lack of appropriate ICT skills, teachers’ unwillingness to advance their computer skills, and preference of use of traditional methods, among others. Some school managers and education stakeholders had not provided requisite facilities and equipment like computers, digital and video cameras, which are key in successful implementation of technology-based lessons. Continuous professional development programs should be developed to build teachers’ capacity in ICT integration into their teaching. Finally, feasible ICT school policies should be put in place to spear head uptake into classroom instruction.